Multifunctional polymeric micelles loaded with doxorubicin and poly(dithienyl-diketopyrrolopyrrole) for near-infrared light-controlled chemo-phototherapy of cancer cells - Liu, Hui (2017)
Polymeric micelles loaded with multiple therapeutic modalities are important to overcome challenges such as drug resistance and improve the therapeutic efficacy. Here we report a new polymer micellar drug carrier that integrates chemotherapy and photothermal therapy in a single platform. Specifically, a narrow bandgap poly(dithienyl-diketopyrrolopyrrole) (PDPP) polymer was encapsulated together with a model anticancer drug doxorubicin (DOX) in the hydrophobic cores of polymeric micelles formed by Pluronic F127, an amphiphilic poly(ethylene oxide)-poly(propylene oxide)-poly(ethylene oxide) triblock copolymer. The PDPP polymer served as an organic photothermal agent that absorbs near-infrared light (700–1000 nm) and transforms into heat efficiently. The dual functional micelles co-loaded with PDPP and DOX in the hydrophobic compartment showed good colloidal stability after being stored at 4 °C at least over two months, and remained visibly stable after 808-nm laser irradiation. The loaded DOX had negligible effect on the size and photothermal property of the micelles. The release of DOX from the micelles could be enhanced by the “breathing” effect of shrinking/swelling of the micelles induced by the temperature change, owing to the thermosensitive nature of the F127 polymers. Importantly, the ternary F127/PDPP/DOX micelles under 808-nm laser irradiation showed enhanced cytotoxicity against cancer cells such as HeLa cells, compared to F127 micelles containing single modality of either PDPP or DOX only.